High Number of Potential Transmitters Revealed in a Population-based Systematic Hepatitis C Virus RNA Screening Among Human Immunodeficiency Virus-infected Men Who Have Sex With Men. (13th August 2018) - Braun, Dominique L; Hampel, Benjamin; Martin, Eileen; Kouyos, Roger; Kusejko, Katharina; Grube, Christina; Flepp, Markus; Stöckle, Marcel; Conen, Anna; Béguelin, Charles; Schmid, Patrick; Delaloye, Julie; et al.
Abstract : We performed a systematic RNA-based screening for hepatitis C virus (HCV) among 3722 human immunodeficiency virus–positive men who have sex with men (MSM). We identified 177 MSM (4.8%) with replicating disease, 24 (14%) of whom had incident infection. Abstract: Background: The proportion of undiagnosed hepatitis C virus (HCV) infections in high-risk populations, such as human immunodeficiency virus (HIV)–infected men who have sex with men (MSM) is unclear. Identification of potential HCV transmitters is important to reach World Health Organization HCV elimination targets. Methods: Between October 2015 and May 2016, we performed a systematic HCV RNA–based screening among HIV-infected MSM participating in the Swiss HIV Cohort Study (SHCS). HCV antibodies were measured from all HCV RNA–positive samples. Results: Of 4257 MSM recorded in the SHCS database, we screened 3722 (87%) by HCV polymerase chain reaction, and 177 (4.8%) harbored a replicating HCV infection. We identified 24 individuals (14%) with incident HCV infection; one-third of them had a negative HCV antibody result at the time of HCV RNA positivity. In a multivariable model, elevated liver enzyme values (odds ratio, 14.52; 95% confidence interval, 9.92–21.26), unprotected sex with occasional partners (2.01; 1.36–2.98), intravenous drug use (7.13; 4.36–11.64), noninjectable drug use (1.94; 1.3–2.88), and previous syphilis diagnosis (2.56; 1.74–3.76) were associated with HCV RNA positivity. Conclusions: A systematic HCV RNA–based screening among HIV-infected MSM revealed a high number of potential transmitters. A substantial subpopulation of MSM had incident infection, one-third of whom had a negative HCV antibody test result at the time of the HCV RNA positivity. These data reveal that one-time RNA testing of a high-risk population for HCV RNA might identify more infected persons than routine testing for HCV antibodies and liver enzymes. Clinical Trials Registration: NCT02785666